School Environment, Obesogenic Factors from the Perspective of the Educational Community at a School in Medellín, Colombia (2020)
Background: The World Health Organization -WHOconsiders obesity among the first causes of death, for conditioning the development of Chronic Noncommunicable Diseases -CNCD-, which in 2016 caused 72% of deaths worldwide. By 2016, the WHO and the World Bank report that the prevalence of excess weight in children exceeds 30% of the population. Early occurrences of these diseases can be preventable from childhood, as they are related to people's lifestyle and exposure to obesogenic environments characterized by food availability and conditions for physical activity, not conducive to health. Children in obesogenic environments will have rapid weight gains and increased risk of obesity in adult life, of up to 50% (Muñoz & Arango, 2017). Objective: To identify the obesogenic factors from the perspective of the educational community, seeking solutions in the prevention of obesity, all the while taking into account the school environment. Ann Nutr Metab 2020;76(suppl 4):1–232 Downloaded from http://karger.com/anm/article-pdf/76/Suppl. 4/1/4020422/000511826.pdf by guest on 01 July 2024 FINUT Virtual Conference 2020 66 Methods: Qualitative research and hermeneutical paradigm; eight focus groups (4 to school children and 4 to teachers) were studied. The analysis was based on fundamental theory. Results: The obesogenic factors identified by the educational community are located at the individual and institutional levels. The first level refers to eating habits, purchasing power, and emotional aspects, which influence the choice and consumption of inappropriate food - both in quantity and quality, by schoolchildren. The second one is the institutional conditions, such as the locative infrastructure, the quality of the food supply, and other issues involving the teachers themselves and the teaching activities and processes, which condition both food intake and physical activity. Conclusions: Identifying the favorable aspects of excess weight in the school environment, based on its microenvironments; provides sufficient and necessary supplies and materials for the construction of a comprehensive educational proposal, taking into account the individual and environmental conditions of the subjects, their practices, knowledge, meanings, and beliefs; aimed at going beyond the transmission of mere knowledge through significant interventions - relevant and consistent with their possibilities-, and actions that transform these environments. Keywords: school/excess/ weight/ environment. Conflicts of interest: none This work is part of the Colon Cancer Prevention (ECNT) project. Educational perspective against obesity, in food, nutrition, and physical activity, in schoolchildren in Antioquia and Quindío, within the Scientific Academic Alliance for the strengthening of IES, focused on nanobioengineering for the prevention, diagnosis, and treatment of ColoncancerNanobiocancer. Scientific Colombia 2017.